2020
DOI: 10.21776/ub.jitode.2020.008.03.09
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Marketing Mix Elements on Ecotourism Clientele - Jimma Zone, Southwest Ethiopia

Abstract: This study assessed the influence of marketing mix elements (7 Ps i.e. Product, Price, Place, Promotion, People, Process and Physical Evidence) on ecotourism clientele in Jimma Zone, South West Ethiopia. According to the data received from the Jimma Zone Cultural and Tourism office, a total of 23 woredas are under the Jimma zone. From these, the researchers selected six, which are endowed with ecotourism resources. The target population for this study was all Government staff working here and the research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…In several cases, researchers from foreign institutions were found, such as Nobukazu Nagakoshi (L. Hakim & Nagakoshi, 2008), David Reeve (Valeriani et al, 2020), Guillaume Tiberghien (Ristiawan & Tiberghien, 2021), and Kumiko Shishido (Sadguna et al, 2020), or where the member researchers are from different international institutions from the first researcher, such as the Hess et al, (2021) article, both of which were ignored, because the data collection only refers to the identity of the first researcher. Twenty-five international researchers were recorded from 15 countries: United States (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Netherlands (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Ethiopia (Eshete et al, 2020), Philippines (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), United Kingdom (Hess et al, 2021), Italy (Brida, 2008), South Korea (Anele & Sam-Otuonye, 2021), Egypt (Abdou et al, 2020), France (Loustaunau, 2018), Romania (Voda et al, 2019), and Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). The authors noticed that the tendency of international scholars to publish their studies in national tourism journals is indicated to have increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several cases, researchers from foreign institutions were found, such as Nobukazu Nagakoshi (L. Hakim & Nagakoshi, 2008), David Reeve (Valeriani et al, 2020), Guillaume Tiberghien (Ristiawan & Tiberghien, 2021), and Kumiko Shishido (Sadguna et al, 2020), or where the member researchers are from different international institutions from the first researcher, such as the Hess et al, (2021) article, both of which were ignored, because the data collection only refers to the identity of the first researcher. Twenty-five international researchers were recorded from 15 countries: United States (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Netherlands (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Ethiopia (Eshete et al, 2020), Philippines (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), United Kingdom (Hess et al, 2021), Italy (Brida, 2008), South Korea (Anele & Sam-Otuonye, 2021), Egypt (Abdou et al, 2020), France (Loustaunau, 2018), Romania (Voda et al, 2019), and Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). The authors noticed that the tendency of international scholars to publish their studies in national tourism journals is indicated to have increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable tourism researchers in Indonesia adopt several statistical quantitative analysis techniques and mathematical calculations. Among them were Linear Regression Analysis techniques (Wirajuna & Supriadi, 2017;Yuniati, 2019), Boullon Mathematical Model for carrying capacity calculation (Luna, 2021), Customer Satisfaction Index (Boka, 2016), Descriptive Statistics Analysis (Arreza & Esguerra, 2021;Irawati, 2019), Gini coefficient (Maulana et al, 2020), Importance Performance Analysis (IPA) (Karo et al, 2020), Moderated Regression Analysis (Putra et al, 2015), Multiple Regressions Analysis (Eshete et al, 2020;Hillary, 2020;Parinusa et al, 2019), Path Analysis (Hermawan, 2017;Laba et al, 2019;Sanjiwani, 2019;Sulthony, 2021), System Dynamics Modeling (Kustiwan & Safrianty, 2012;Tangian et al, 2015), Principal Component Analysis (Arisanty et al, 2020), and Structural Equation Modeling (Yustita et al, 2020). However, a closer look at the data indicates that several quantitative studies did not include calculations in the manuscript (Narayana et al, 2020;Zakiyah & Kurniawan, 2014).…”
Section: Research Methods Used By Sustainable Tourism Researchersmentioning
confidence: 99%
See 1 more Smart Citation
“…25 peneliti internasional berasal dari 15 negara: Amerika Serikat (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Belanda (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Etiopia (Eshete et al, 2020), Filipina (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), Inggris (Hess et al, 2021), Italia (Brida, 2008), Korea Selatan (Anele & Sam-Otuonye, 2021), Mesir (Abdou et al, 2020), Prancis (Loustaunau, 2018), Rumania (Voda et al, 2019), dan Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). Dari frekuensi artikel bisa dilihat bahwa kecenderungan akademisi internasional untuk mempublikasikan kajian mereka pada jurnal pariwisata nasional terindikasi meningkat pada beberapa tahun terakhir.…”
Section: Diskusiunclassified
“…Beberapa teknik analisis kuantitatif statistik dan penghitungan matematika dikaji oleh peneliti pariwisata berkelanjutan di Indonesia. Diantaranya adalah teknik Analisis Regresi Linear (Wirajuna & Supriadi, 2017;Yuniati, 2019), Model Matematika Boullon untuk penghitungan Daya Dukung (Luna, 2021), Customer Satisfaction Index (Boka, 2016), Descriptive Statistics Analysis (Arreza & Esguerra, 2021;Irawati, 2019), Gini coefficient (Maulana et al, 2020), Importance Performance Analysis (IPA) (Karo et al, 2020), Moderated Regression Analysis (D. P. K. E. Putra et al, 2015), Multiple Regressions Analysis (Eshete et al, 2020;Hillary, 2020;Parinusa et al, 2019), Path Analysis (Hermawan, 2017;Laba et al, 2019;Sanjiwani, 2019;Sulthony, 2021), System Dynamics Modeling (Kustiwan & Safrianty, 2012;Tangian et al, 2015), Principal Component Analysis (Arisanty et al, 2020), dan Structural Equation Modelling (Yustita et al, 2020). Namun penulis juga menemukan dimana terdapat kajian kuantitatif yang tidak mencantumkan perhitungan di dalam manuskripnya, diantaranya adalah karya Narayana et al, (2020) dan Zakiyah & Kurniawan (2014).…”
Section: Diskusiunclassified